Insufficient/inadequate category in breast cytology: Are the standardized guidelines of rapid on‐site evaluation available to reduce its rate?. Issue 5 (18th March 2023) - Bharti, Jyotsna Naresh; Nigam, Jitendra Singh; Rath, Ashutosh; Pradeep, Immanuel
Abstract: In 2017, the International Academy of Cytology announced a five‐tier reporting system for breast fine‐needle aspiration biopsy (FNAB) cytopathology. We observed the insufficient/inadequate cases rate varied from 2.05% to 39.89%, with a risk of malignancy varying from 0% to 60.87%. This wide range of variation poses a significant number of patients at risk due to delay in management. Some authors describe rapid on‐site evaluation (ROSE) as a tool to reduce its rate. In this preliminary review, we also observed that there were no uniform guidelines available for ROSE to reduce the insufficient/inadequate category rate. We expect that cytopathologists will construct some uniform guidelines for ROSE in the future, which may help to reduce the rate of category 1.